Anatomical, Histological and Histochemical Investigation of Soft Palate in Cat (Felis Catus Domesticus.L) - Abbas Lafi Batah 1, Hussein Bashar Mahmood 2 , Walaa F Obead3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The aim of this study was to evaluate the normal structure and provide distribution for palatine glands in cranial and caudal part of soft palate. Also, afford information to be useful for both surgical interventions and pathological disease. Method/: Sixth healthy cats were caught in Iraq farms. All experimental animals euthanized by intramuscular injection of ketamine (0.5 cc) and xylazine (0.5 cc), Sections were stained by H&E and combined AB+PAS stain 2.5 pH. Results: The soft palate was triangular in shape, the dimensions was (2.8, 2) cm in length and width respectively. Also, had two surface; nasopharyngeal surface lined by psuedostratified columnar epithelial ciliated and oropharyngeal surface lined by stratified squamous epithelia. The palatine glands appeared magenta in color during staining by AB+PAS combined stain due to neutral secretion. Conclusion: The palatine glands variance in distribution between dorsal and ventral surface of soft palate, most of these glands constricted in oropharyngeal surface.